Dynamic modelling of wind turbine gearbox bearing loading during transient events. Issue 7 (1st September 2015) - Bruce, Thomas; Long, Hui; Dwyer‐Joyce, Rob S.
Abstract : Wind turbine gearbox bearings (WTGBs) are the most reliability critical component in wind turbine gearboxes because of their high failure rate and long downtime‐per‐failure. Current design methods predict bearing failure‐by‐fatigue life models. However, premature WTGB failures have been observed by many other modes. This study presents the development of a multibody dynamic gearbox model, used to determine maximum bearing contact stresses from laboratory measured shaft torque data during normal operation and shutdown conditions. The model was validated by comparing its results to other models of the 750 kW National Renewable Energy Laboratory test drive train by the Gearbox Reliability Collaborative. During normal operation, the maximum contact stress experienced by the planetary stage bearings exceeded recommended levels by 1% and during shutdown by 15%. High‐speed shaft bearings also exceeded recommended levels during shutdown by 18%.